Validação da técnica de avidez de IgG em amostras de sangue de recém-nascidos coletadas em papel filtro: valor prognóstico para indicação de infecção ativa pelo Toxoplasma gondii - Souza, Jéssica Yonara de (2017)
Congenital toxoplasmosis is an infectious disease that results from the transplacental transfer of the protozoan Toxoplasma gondii to the concept and can cause serious fetal damage, its diagnosis and complex, and the sooner realized improves the prognosis of infection. The evaluation of IgG avidity is used as an indicator of recent infection mainly in the follow-up of pregnant women at risk, and to date it is not established for use in blood samples of newborns and in blood samples collected on filter paper. The general objective of this study was to evaluate the prognostic importance of the IgG avidity test in sera and in blood collected on RN filter paper in the indication of T. gondii congenital infection. Blood samples were collected on RN filter paper at the Hospital das Clínicas-UFG, Dona Íris Maternity Hospital, Goiânia-GO and Cais Nova Era, Aparecida de Goiânia-GO Serological screening for IgG and IgM antibodies was performed using the Elisa test (BIOLISA® toxoplasmosis IgG and IgM kit). From the total of 1277 samples, two IgM positive samples were detected, in 564 samples (44.1%) the presence of IgG was detected, and the ELISA ≥3.0, 57.67% (327 / 567), 177 pairs of mother and child recolects were performed to confirm the results obtained on filter paper and IgG avidity evaluation. In 167 pairs (94.36%) IgG detection was confirmed by demonstrating good sensitivity of the method, in 4 (2.40%) samples the IgG of the newborn presented low avidity of IgG antibody that is indicative of recent infection. In 17 samples the collection was performed simultaneously on filter paper and peripheral blood, in order to evaluate the efficacy of the avidity technique in filter paper samples, the agreement between the results was 100%. Screening of high IgG NB associated with the avidity test can be performed on filter paper and this method may contribute to the early detection and diagnosis of toxoplasmosis.